Solving the Traveling Tournament Problem with Iterative-Deepening A* - Uthus, David; Riddle, Patricia; Guesgen, Hans (Proceedings of the International Conference on Automated Planning and Scheduling, 2013)
We give an overview of our journal paper on applying iterative-deepening A* to the traveling tournament problem, a combinatorial optimization problem from the sports scheduling literature. This approach involved combining past ideas and creating new ideas to help reduce node expansion. This resulted in a state-of-the-art approach for optimally solving instances of the traveling tournament problem. It was the first approach to solve the classic NL10 and CIRC10 instances, which had not been solved since the problem’s introduction.